Digital Transformation through Big Data: Implications for Global Product Development - Sunandar (Novatio : Journal of Management Technology and Innovation, 2024)
Big Data and Predictive Analytics (BDPA) have emerged as transformative forces in product development, creating opportunities to enhance innovation, efficiency, and resilience. This review highlights BDPA’s contributions to value creation by improving customer insights, optimizing design, strengthening operational efficiency, and mitigating risks. It synthesizes empirical and conceptual studies from multidisciplinary databases to demonstrate how BDPA shapes competitiveness across sectors. Comparative findings reveal adoption disparities between advanced and emerging economies, where infrastructural and skill-related constraints limit effectiveness. Addressing these barriers requires investment in human capital, cross-departmental collaboration, and supportive policy frameworks. Future research should prioritize longitudinal and sector-specific approaches to better capture BDPA’s sustained impacts and contextual dynamics.